Culdoscopy in sterility - Ascenzo Cabello, Jorge (2015)
This work was made in the Peruvian Fertility Center and the authors stated their experience over 200 steril women. Culdoscopy is more useful in the diagnostic study of the steril women than in the gynecological cases. The end results obtained are the same of other authors. Pathologic conditions of the ovaries or tube were found in 50%; uterus was abnormal one of every four and adhesive inflammation in one of every three examinations unsuspected clinically. Culdoscopy is emphasized as an important method used in the diagnosis and, same times, in the treatment.